PELATIHAN PENYUSUNAN STRATEGI BISNIS BERBASIS BUSINESS MODEL CANVAS PADA INDUSTRI GULA AREN DI NAGARI TALANG ANAU, SUMATERA BARAT - Wisnubroto, Muhammad Parikesit; Lubis, Muhammad Iqbal Abdi; Yulianto, Kiki; Anwar, Aswaldi; Havifi, Ilham; Sari, Lusi Puspika; Hasibuan, Halimatus Syahdia; Ramadhani, Lembayung Maghfira; Silvadriyanto, Reihan; Adhevin, Shadiq Octaryan; Rivandi, Oktavia; Adib, Muhammad (Universitas Mataram, 2024)
Nagari Talang Anau Tourism Village is one of the palm sugar producing areas that has been known for a long time by the community. In this area, there are many sugar palm trees and several small industries engaged in processing sap into palm sugar. However, the industry has not developed optimally and still uses conventional methods for its business management strategy. Therefore, we carried out training activities to prepare a business strategy based on the business model canvas (BMC) to the people of Nagari Talang Anau. The training was conducted using the lecture method by the speaker about BMC and continued with direct practice of BMC preparation. Some of the facilities and infrastructure supporting this service activity include stationery, BMC material, loudspeakers, laptops, and projectors. During the presentation, participants seemed enthusiastic to the material presented. The discussion went in two directions which was marked by the emergence of various questions related to BMC. The BMC consists of 9 elements including target market, consumer value proposition, channels, consumer relationships, revenue sources, main activities, human resources, cooperation, and cost structure. Through this preparation, it is expected to be able to identify the strengths and weaknesses of the business that has been carried out and help the palm sugar industry to focus and be rational in determining business development targets.